2019
DOI: 10.1128/aac.01782-19
|View full text |Cite
|
Sign up to set email alerts
|

Ceftolozane Pharmacokinetics in a Septic Critically Ill Patient under Different Extracorporeal Replacement Therapies

Abstract: Ceftolozane pharmacokinetics in a septic critically ill patient under different extracorporeal replacement therapies. Antimicrob Agents Chemother 64:e01782-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Overall, the search strategy identified 70 articles that were assessed for eligibility. Fifty-five of these articles did not fulfil the inclusion criteria, resulting in the inclusion of 15 original studies (3 population PK studies and 12 case reports) [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] assessing the PK behaviour of novel agents in critically septic patients requiring CRRT (Fig. 1).…”
Section: Pharmacokinetics (Pk) Of Novel Antibiotics In Patients Undermentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the search strategy identified 70 articles that were assessed for eligibility. Fifty-five of these articles did not fulfil the inclusion criteria, resulting in the inclusion of 15 original studies (3 population PK studies and 12 case reports) [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] assessing the PK behaviour of novel agents in critically septic patients requiring CRRT (Fig. 1).…”
Section: Pharmacokinetics (Pk) Of Novel Antibiotics In Patients Undermentioning
confidence: 99%
“…One population PK study and seven case reports assessed the PK behaviour of ceftolozane-tazobactam in 13 different critically patients requiring CRRT, including one child [24,[27][28][29][30][31][32][33]. Different dosing schedules (1.5 g or 3 g every 8 h) were administered.…”
Section: Ceftolozane-tazobactammentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 83 studies included in the SLR, 61 were published as peer-reviewed publications [ 18 78 ], and 22 were conference proceedings (availability as abstracts or posters) [ 79 – 100 ]. Including studies that recruited patients from multiple countries, the most common study locations were the US (N = 50), [ 21 , 22 , 24 , 27 29 , 33 , 34 , 39 41 , 43 45 , 50 , 51 , 54 , 56 , 57 , 59 , 61 , 62 , 68 71 , 73 – 77 , 79 – 85 , 87 – 92 , 94 , 95 , 97 – 100 ] Spain (N = 15) [ 26 , 28 , 30 32 , 35 37 , 42 , 47 , 49 , 58 , 66 , 79 , 96 ], and Italy (N = 13) [ 18 , 20 , 23 , 25 , 48 , 52 , 53 , 55 , 64 , 67 , 72 , 79 , 86 ]. A variety of study designs were captured: 27 were non-comparative retrospective studies [ 18 , 19 , 22 ,…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this review identified 30 publications reporting a total of 364 immunocompromised patients [ 22 , 26 , 27 , 30 , 34 , 37 39 , 41 , 43 , 48 , 49 , 51 , 53 , 59 61 , 63 , 68 , 73 , 79 , 83 – 86 , 90 , 91 , 96 – 98 ]. Immunocompromised patients include those with a history of organ transplant, disease suppressing immunity (e.g.…”
Section: Resultsmentioning
confidence: 99%